Respuestas

2013-05-18T17:48:01+02:00
3x-y=5y                                   x+3y/2=5
3x=5y+y                                   3y/2=5-x
3x=6y                                         3y=(5-x)2
3/6x=y                                         y=(5-x)2/3
1/3x=y                                         y= 10/3-2/3x

ahora igualamos:      1/3x        = 10/3-2/3x
                               1/3x+2/3x=10/3
                                3/3x       =10/3
                                     x       =10/3